The Role of GnRH analogues in endometriosis associated apoptosis and angiogenesis - Tesone, Marta (2008)
It has been postulated that gonadotropin-releasing hormone (GnRH) analogues may act directly on endometrial cells and inhibit their growth and proliferation by regulation of apoptotic and angiogenic mechanisms. Eutopic endometrial cells from patients with endometriosis show an increased proliferation rate and are less susceptible to cell death by apoptosis than those from subjects without the disease. Notably, the GnRH analogue, leuprorelin, inhibits cell proliferation and increases the apoptotic rate in eutopic endometrial cell cultures, an effect that appears to be mediated by an increase in the expression of the pro-apoptotic proteins Bax and FasL and a decrease in the expression of the anti-apoptotic protein Bcl-2. Angiogenesis is an important process in the development of endometrial tissue, and it is regulated by vascular endothelial growth factors (VEGFs) and angiopoietins. VEGF levels are elevated in peritoneal fluid and endometriotic tissue from patients with endometriosis. In addition, it has been demonstrated that the expression of VEGF is potentiated by a variety of cytokines, including IL-1beta. Recent studies show that leuprorelin reduces the production of VEGF-A and IL-1beta in eutopic endometrial cell cultures, suggesting a mechanism by which it could inhibit the development of endometriosis. Thus, GnRH analogues appear to be effective in reducing the growth of endometrial cells, not only due to their classical pituitary endocrine effects, but also via a direct effect on the endometrial cells themselves.